A CD45 polymorphism associated with abnormal splicing is absent in African populations. - Tchilian, E; Dawes, R; Ramaley, P; Whitworth, J; Yuldasheva, N; Wells, R; Watera, C; French, N; Gilks, C; Kunachiwa, W; Ruzibakiev, R; Leetrakool, N; et al. (2002)
The CD45 antigen is essential for normal antigen receptor-mediated signalling in lymphocytes, and different patterns of splicing of CD45 are associated with distinct functions in lymphocytes. Abnormal CD45 splicing has been recognized in humans, caused by a C77G transversion in the gene encoding CD45 (PTPRC). Recently the C77G polymorphism has been associated with multiple sclerosis and increased susceptibility to HIV-1 infection. These studies suggest that the regulation of CD45 splicing may be critical for the proper function of the immune system. Because of these data we examined the frequency of the C77G allele in African and Asian populations from countries with high or low prevalence of HIV infection. Here we report that the variant CD45 C77G allele is absent in African populations. We further show that populations living in the Pamir mountains of Central Asia have a very high prevalence of the C77G variant.